DNA methylation and gene expression changes in mouse mammary tissue during successive lactations: part I – the impact of inflammation - E. Ivanova; C. Hue-Beauvais; A. Chaulot-Talmon; J. Castille; J Laubier; C De Casanove; A. Aubert-Frambourg; P. Germon; H. Jammes; F. Le Provost (Epigenetics, 2023)
Mastitis is among the main reasons women cease breastfeeding, which leads to them supplementing breast milk with artificial formula. In farm animals, mastitis results in significant economic losses and the premature culling of some animals. Nevertheless, researchers do not know enough about the effect of inflammation on the mammary gland. This article discusses the changes to DNA methylation in mouse mammary tissue caused by lipopolysaccharide-induced inflammation (4 h post-injection of lipopolysaccharide). We analysed the expression of some genes related to mammary gland function, epigenetic regulation, and the immune response. The analysis focused on three comparisons: inflammation during the first lactation, inflammation during second lactation with no history of inflammation, and inflammation during second lactation with previous inflammation. We identified differentially methylated cytosines (DMCs), differentially methylated regions (DMRs), and some differentially expressed genes (DEGs) for each comparison. The three comparisons shared some DEGs; however, few DMCs and only one DMR were shared. These observations suggest that inflammation is one of several factors affecting epigenetic regulation during successive lactations. Furthermore, the comparison between animals in second lactation with and without inflammation, with no inflammation history during first lactation showed a different pattern compared to the other conditions in this experiment. This indicates that inflammation history plays an important role in determining epigenetic changes. The data presented in this study suggest that lactation rank and previous inflammation history are equally important when explaining mammary tissue gene expression and DNA methylation changes. Abbreviations: RRBS, reduced representation bisulfite sequencing; RT–qPCR, real-time quantitative polymerase chain reaction; MEC, mammary epithelial cells; TSS, transcription start site; TTS, transcription termination site; UTR, untranslated region; SINE, short interspersed nuclear element; LINE, long interspersed nuclear element; CGI, CpG island; DEG, differentially expressed gene; DMC, differentially methylated cytosine; DMR, differentially methylated region; GO term, gene ontology term; MF, molecular function; BP, biological process